2002
DOI: 10.1115/1.1478058
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Thermal Conductivity on the Heat Transfer Performance in a Heat Sink

Abstract: An extensive numerical analysis of the temperature distribution and fluid flow in a heat sink currently being used for cooling desktop computers was conducted, and demonstrated that if the base of a heat sink was fabricated as a heat pipe instead of a solid material, the heat transfer performance could be significantly increased. It was shown that as the heat sink length increases, the effect of the thermal conductivity of the base on the heat transfer performance increases to be a predictable limit. As the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Ma and Peterson [4] have used an effective thermal conductivity to model the heat sink base embedded with a heat pipe and obtained a good agreement with experimental data. With a given forced convection for a heat sink, the heat transfer coefficient is given.…”
Section: Theoretical Analysismentioning
confidence: 74%
See 2 more Smart Citations
“…Ma and Peterson [4] have used an effective thermal conductivity to model the heat sink base embedded with a heat pipe and obtained a good agreement with experimental data. With a given forced convection for a heat sink, the heat transfer coefficient is given.…”
Section: Theoretical Analysismentioning
confidence: 74%
“…From the data obtained experimentally by Ma and Peterson [4], the effective convective heat transfer coefficient was determined for the fins by Eq. (5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Fig. 2-a, the airflows entered the entry plenum chamber (1) in which the meshes and honeycomb were installed. The cross sectional area of the entry plenum chamber (1) was greater than those of heat transfer test sections with wavy and flat walls.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the further increase of cooling duty for a fin array requires the reduction of conductive and/or convective resistances. The theoretical analysis with assumption of extremely high material conductivity of fin arrays [1] revealed that the cooling performance with increased material conductivity was constrained by the available convective capability of the fin array. Convective cooling performances of fin arrays thus play important roles for this type of cooling application.…”
Section: Introductionmentioning
confidence: 99%